SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

A 500-year cycle of demographic expansion and contraction in the lower Yangtze and adjacent coastal region during the Holocene driven by East Asian summer monsoon oscillations - Deke Xu; Yuhai Wang; Keyang He; Hao Li; Yajie Dong; Jun Kuang; Zhigang Zhang; Bing Song; Yulong Niu; Guoping Sun; Yonglei Wang; Jiatong Lu; et al. (Quaternary Science Reviews, 2026)

Insights into the effects of different nitrogen sources on microbial metabolic function and biodegradation of bituminous coal - Yundu Yang; Bingjun Liu; Sheng Xue; Junyu Wang; Xiangqing Jiang; Ruifeng Chen; Rui Sun; Keyang Cheng (Fuel, 2026)

Fibrils aggregation induced the conformationally flexible regions of rice bran protein to improve its stability of emulsion gel - Keyang Sun; Wanyue Jiang; Junqi Pang; Xuesi Pan; Zhongman Min; Qingyu Yang; Yuzhe Gao (Innovative Food Science & Emerging Technologies, 2025)

Unveiling role of accumulation by various submerged plants in removal of per- and polyfluoroalkyl substances from reclaimed water - Lin Chen; Qian Wang; Yuanyuan Li; Xin Shan; Keyang Wu; Cuizhu Sun; Lingyun Chen; Fengmin Li (Bioresource Technology, 2025)

Target-Defense Games with One or Two Unmanned Surface Vehicles Defending an Island: A Geometric Analytical Approach - Keyang Wang; Yintao Wang; Qi Sun (Journal of Marine Science and Engineering, 2025)
This paper considers a target-defense game in an open area with one or two defenders as well as an intruder. The intruder endeavors to reach the boundary of the island, while the defenders strive to prevent that by capturing the intruder through contact. Islands, as closed areas, restrict the free movement of the defenders, since the defenders—represented by USVs—cannot traverse the target area directly. First, we are concerned with the barrier, which is the boundary of the winning zones, taking into account the impact of the target. For the initial states lying in the defenders’ winning zone, there exists a strategy for the defenders to intercept the intruder regardless of the intruder’s best effort, while for the initial states lying in the intruder’s winning zone, the intruder can always invade successfully. We propose a geometric method to construct the barrier analytically for two kinds of speed ratios. Then, by taking index functions into consideration, we present optimal strategies for the players after constructing the dominance regions when their initial states lie in different winning zones. Simulation results verify the effectiveness of the proposed method. This study can be extended to scenarios involving multiple defenders.

Surface free radicals activated CoP/MoS2 sensors through electrocatalytic water splitting for enhanced NO2 sensing at room temperatures - Xixi Li; Xiao Wang; Zhaokun Sun; Feifei Li; Yao Fu; Keyang Zhao; Gang Zhao; Cunguang Zhu; Xijin Xu (Chemical Engineering Journal, 2024)

Geographic mosaics of rice domestication in the lower Yangtze River indicated by morphological characteristics of rice bulliform phytoliths - Keyang He; Yonglei Wang; Yunfei Zheng; Guoping Sun; Shao Lei; Yongning Li; Xiaoshan Yu; Jianping Zhang; Houyuan Lu (Archaeological and Anthropological Sciences, 2024)

Novel Selective Quantification of Zinpentraxin Alfa Biotherapeutic in the Presence of Endogenous Isomer in Plasma Samples of Idiopathic Pulmonary Fibrosis Patients Using Immunoaffinity LC–MS - Maoyin Li; Audrey Arjomandi; Xiaowei Sun; Erhu Lu; Tulika Tyagi; WeiYu Lin; Saloumeh K. Fischer; Surinder Kaur; Keyang Xu (The AAPS Journal, 2023)
Idiopathic pulmonary fibrosis (IPF) is a progressive fatal interstitial lung disease that affects three million patients worldwide and currently without an effective cure. Zinpentraxin alfa, a recombinant human pentraxin-2 (rhPTX-2) protein, has been evaluated as a potential drug candidate for the treatment of IPF. Clinical pharmacokinetic analysis of zinpentraxin alfa has been challenging historically due to interference from serum amyloid P component (SAP), an endogenous human pentraxin-2 protein. These molecules share an identical primary amino acid sequence and glycan composition; however, zinpentraxin alfa possesses α2,3-linked terminal sialic acid residues while SAP is an α2,6-linked isomer. By taking advantage of this only structural difference, we developed a novel assay strategy where α2,3-sialidase was used to selectively hydrolyze α2,3-linked sialic acid residues, resulting in desialylated zinpentraxin alfa versus unchanged sialylated SAP, following an immunoaffinity capture step. Subsequent tryptic digestion produced a unique surrogate asialo-glycopeptide from zinpentraxin alfa and allowed specific quantification of the biotherapeutic in human plasma. In addition, a common peptide shared by both molecules was selected as a surrogate to determine total hPTX-2 concentrations, i.e., sum of zinpentraxin alfa and SAP. The quantification methods for both zinpentraxin alfa and total hPTX-2 were validated and used in pharmacokinetic assessment in IPF patients. The preliminary results suggest that endogenous SAP levels remained largely constant in IPF patients throughout the treatment with zinpentraxin alfa. Our novel approach provides a general bioanalytical strategy to selectively quantify α2,3-sialylated glycoproteins in the presence of their corresponding α2,6-linked isomers. Graphical Abstract

Ambient PM2.5, ozone and mortality in Chinese older adults: A nationwide cohort analysis (2005–2018) - Yunquan Zhang; Zhouxin Yin; Shaojie Li; Junfeng (Jim) Zhang; Haitong Zhe Sun; Keyang Liu; Kokoro Shirai; Kejia Hu; Chengxuan Qiu; Xiaoyun Liu; Yachen Li; Yi Zeng; et al. (Journal of Hazardous Materials, 2023)

Multi-proxy evidence of environmental change related to collapse of the Liangzhu Culture in the Yangtze Delta, China - Keyang He; Houyuan Lu; Guoping Sun; Xiang Ji; Yonglei Wang; Kaikai Yan; Xinxin Zuo; Jiangping Zhang; Bin Liu; Ningyuan Wang (Science China Earth Sciences, 2021)

Variegated transnational partnerships: Multi-scalar actor networks in China’s overseas industrial parks - Tao Song; Man Sun; Yutian Liang; Soavapa Ngampramuan; Yeerken Wuzhati; Keyang Zhou (Journal of Geographical Sciences, 2021)

Design and one-pot synthesis of 2-thiazolylhydrazone derivatives as influenza neuraminidase inhibitors - Keyang Yuan; Mengwu Xiao; Ying Tan; Jiao Ye; Yongle Xie; Xiaoxiao Sun; Aixi Hu; Wenwen Lian; Ailin Liu (Molecular Diversity, 2017)

Reduction of pentavalent antimony by trypanothione and formation of a binary and ternary complex of antimony(III) and trypanothione - Siucheong Yan; Fei Li; Keyang Ding; Hongzhe Sun (JBIC Journal of Biological Inorganic Chemistry, 2003)